Factores asociados a las úlceras por presión según escala de prevención de riesgo, en pacientes del servicio de medicina - Romero Torres, Aswel (2023)
The objective was to determine the factors associated with pressure ulcers according to the risk prevention scale in patients of the Medicine service. The method was quantitative with a non-experimental descriptive correlational design. The sample was 83 patients determined through the finite population formula. The technique was the interview and the instruments were the Data Sheet on Intrinsic and Extrinsic Factors in Hospitalized People and the Braden Pressure Ulcer Risk Prevention Scale. For the correlational analysis, the Chi Square statistical test was used with a level of significance of α = 0.05. The results were: 75.35% were over 65 years old, 55.3% were female, 22.4% had infectious disease as a diagnosis of admission, 17.8% heart disease and 7.1% Other diseases underlying disease hypertension 48.2%, diabetes 30.6 % and cancer 1.2%, the degree of dependence 61.2% had grade IV. In conclusion, statistical significance was found with Kendall's age B, (p < 0.05) a of p = 0.018, admission diagnosis, Pearson's X2, (p < 0.05) with neurological disease a p = 0.033, kidney disease p = 0.044 and with heart disease, p = 0.042, likewise no significant association (p > 0.05) was found with infectious disease p = 737 and other diseases p = 0.935.